Alternatives to downsizing - Cascio, Wayne F. (Henry Stewart Talks, 2014)
When downsizing is unavoidable, Some alternatives to layoffs, Good management in bad times – DuPont – Actions to conserve cash, Reflexite, Business decline contingency plan: stages – Rethink rewards – Instead of more money: more power, Great companies never lose sight of their values, When restructuring is necessary, The 3Cs of success